Pemanfaatan Digitalisasi Dakwah (Studi Penelitian Media DAI Persatuan Islam) - Andri Hendrawan (Lembaga P3M, 2021)
Digitalization of dakwah as a movement of information transformation from analog to digital to disseminate information and broadcast Islamic teachings related to faith, worship, and muamalah in a syumuli (comprehensive) and kaffah (perfect) manner which is presented in a communication medium in digital format, both in the form of internet, media social, website, blog, online TV and online radio. The preachers and preachers who do not use the digitalization of da'wah at the present time certainly need a lot of time and money in conveying their da'wah messages. If you take advantage of the digitalization of da'wah, a preacher can design a variety of da'wah materials (content), as well as the use of preachers from Islamic organizations called Persatuan Islam (Persis). This study aims to examine the digitization of da'wah carried out by Persis preachers / preachers. The research method uses a qualitative method with a descriptive approach, with the research technique of collecting data through observation, interviews, literature study, then analyzing the data that has been collected to make a conclusion. The results of this study indicate that the Islamic Union (Persis) is still concerned about the da'wah movement, in this case oral and written preaching (da'wah bi al-Lisan and bi al-kitabah), using digital da'wah media. Da'wah activists / dai Persis in utilizing digital technology to make da'wah materials already appear to have the ability (skills) to optimize internet network-based computers or laptops, although in designing digital material materials must be assisted by qualified human resources in the field of digital device technology to raise da'wah content to social media applications such as Facebook, Instagram, and Youtube.